ОБРАЗЦЫ ЛИТЕРАТУРЫ И ПЕРЕВОДЫ МАЛОЧИСЛЕННЫХ НАРОДОВ, ПРОЖИВАЮЩИХ В АЗЕРБАЙДЖАНЕ (Konferensiyalar | Conferences, 2023)
Historically in Azerbaijan all peoples, national minorities and ethnic groups are treated equally, without discrimination. The Azerbaijani state pursues a consistent and correct national policy and has achieved important achievements in the field of ensuring the rights of national minorities. Purposeful steps taken by the state, regardless of religion and nationality, have further strengthened the traditions of living as a friendly family, friends and brothers at all times of the Azerbaijani people. Victories won in conditions of unity and equality have been a source of national pride for the Azerbaijani people for centuries. The Azerbaijani people have always believed in the strength of the hand, the inviolability of unity, they have proven this with their deeds and lived by proverbs. It is no coincidence that we celebrated the third anniversary of our great Victory.